Quantification of flavonoids, minerals, and pigments present in “Nanicão” bananas during the ripening process - de Souza, Angela Vacaro [UNESP]; Favaro, Vitória Ferreira da Silva [UNESP]; de Mello, Jéssica Marques [UNESP]; dos Santos, Felipe André [UNESP]; Dall'Antonia, Giseli Boiam [UNESP]; Vicente, Eduardo Festozo [UNESP] (Wiley, 2024)
Abstract: Banana is one of the most consumed and popular fruits in all regions of the world, being cultivated mainly in tropical countries. It is not only a rich source of vitamins A, C, and B, calcium, iron, potassium, phosphorus, and other vitamins and nutrients, but it also contains several types of antioxidants with high nutritional value. In this context, the current study aimed to quantify the content of ascorbic acid, flavonoids, pigments, and minerals present in “Nanicão” bananas during the ripening process. As demonstrated, the level of flavonoids was higher in ripe and overripe fruits, whereas the mineral composition was high only at ripening stage 4 (more yellow than green) a stage that should be prioritized when recommending fruit consumption to the population deficient in these minerals. Regarding pigments, there was a reduction in chlorophylls a and b and an increase in carotenoids and anthocyanins in peels and pulps. Practical Application: Flavonoids are phenolic, bioactive compounds with proven antioxidant and anti-inflammatory activity and products of the plant's secondary metabolism. The degradation of chlorophylls and synthesis of carotenoids and anthocyanins, and as a consequence of the latter pigment, the increase in flavonoids in the pulp was evident during the monitoring of ripening, mainly in the fruit peels in relation to pigments. Minerals are essential elements, the main ones provided in balanced diets and important for dietary and nutritional health.
Keywords: antioxidant compounds; bioactive compounds; mineral composition; Musa spp; ripening stages